Florence, Arizona Immigration and Refugee Rights Project and the Florence Immigration Detention Center - Simmons, William (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
In preparation for our visit to Florence each group will be required to do specific research on specific issues of immigration and asylum law. Then, each group will be required to create a poster on that issue for display at the Migrants, Justice, and the Border event on campus (www.west.asu.edu/borderjustice).